A ternary of paradoxes the magnetick cure of wounds, nativity of tartar in wine, image of God in man / written originally by Joh. Bapt. van Helmont, and translated, illustrated, and ampliated by Walter Charleton, Doctor in Physick, and physician to the late king. [electronic resource] :
Summary goes here